The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/dev.21372
|View full text |Cite
|
Sign up to set email alerts
|

Developmental fluoxetine and prenatal stress effects on serotonin, dopamine, and synaptophysin density in the PFC and hippocampus of offspring at weaning

Abstract: Selective serotonin reuptake inhibitor medication exposure during the perinatal period can have a long term impact in adult offspring on neuroplasticity and the serotonergic system, but the impact of these medications during early development is poorly understood. The aim of this study was to determine the effects of developmental exposure to the SSRI, fluoxetine, on the serotonergic system, dopaminergic system, and synaptophysin density in the prefrontal cortex and hippocampus, as well as number of immature n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 84 publications
3
27
0
2
Order By: Relevance
“…However, when maternal behavior was assessed after perinatal administration of the SSRI paroxetine via drinking water in rats, there were minimal effects of drug treatment on maternal activities like grooming and nursing (Glover et al, 2015). It is important to note that ADs can impact neuroendocrine signaling; hormonal alterations can affect neurotrophic factors and monoamines in pregnant rats that may influence offspring in utero (Bagdy, 1996;Delarue et al, 2001;Fuller, 1996;Gemmel et al, 2016;Morrison et al, 2004;Rayen et al, 2015Rayen et al, , 2013. Moreover, it is possible that pups experienced drug withdrawal after treatment stopped on P21, resulting in effects similar to those observed in human infants with neonatal abstinence syndrome (Forsberg et al, 2014;Klinger et al, 2011;Levinson-Castiel et al, 2006), but such potential effects were not measured in the pups.…”
Section: Discussionmentioning
confidence: 99%
“…However, when maternal behavior was assessed after perinatal administration of the SSRI paroxetine via drinking water in rats, there were minimal effects of drug treatment on maternal activities like grooming and nursing (Glover et al, 2015). It is important to note that ADs can impact neuroendocrine signaling; hormonal alterations can affect neurotrophic factors and monoamines in pregnant rats that may influence offspring in utero (Bagdy, 1996;Delarue et al, 2001;Fuller, 1996;Gemmel et al, 2016;Morrison et al, 2004;Rayen et al, 2015Rayen et al, , 2013. Moreover, it is possible that pups experienced drug withdrawal after treatment stopped on P21, resulting in effects similar to those observed in human infants with neonatal abstinence syndrome (Forsberg et al, 2014;Klinger et al, 2011;Levinson-Castiel et al, 2006), but such potential effects were not measured in the pups.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, maternal postpartum FLX can impact development of female endocrine physiology which could alter hippocampal plasticity. It should be noted that different studies using a lower dose of FLX (5 mg/kg; s.c.) in dams found that maternal postpartum FLX has no effect on density of DCX-expressing cells in males or females at weaning [56], in adolescence [17], or in adulthood ([58]; only males examined). This suggests that only higher doses of FLX alter density of DCX-expressing cells in pre-adolescent offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Research in the hippocampus (a brain area that has received the most attention in animal models of PPD due to its relationship with depression and high degree of plasticity in adulthood) shows alterations in its neurogenesis and dendritic plasticity after stress in the peripartum period [54, 55,57,61]. In line with clinical work, animal models are also pointing to pivotal roles for central serotoninergic system and the hypothalamic-pituitary-adrenal system in postpartum depression [62,63], although much more research is needed in this area.…”
Section: ) Findings From Laboratory Rodent Modelsmentioning
confidence: 99%